Optimalisasi Sistem Perawatan Dan Perbaikan Terencana Mesin Produksi Berdasarkan Analisis Keandalan Pada Pltd Hatiwe Kecil Kota Ambon - Demmatacco, Frederik; Soeparman, Sudjito; Soenoko, Rudy (Rekayasa Mesin, 2013)
Based on preliminary surveys, PLTD X has been operated long enough so that the generator engines often impaired even cause damages during operation. Even maintenance system contained in the PLTD X also has not done, which means there decrease in the production of electrical power generated.Maintenance activities that have been performed by PLTD X is the replacement of engine components damaged as a rejuvenation effort and overhaul that aims to extend the lifespan of the machine, but it is also the act of Preventive maintenance which aims to treat the machines that do not damage or interruption in operation. The dispute resolution process is the method for analyzing the Reliability Centered Maintenance component failure with FBD, System function and functional failure, FMEA and RCM Decision Worksheet. It also can determine the value of Mean Time To Failure (MTTF) and Mean Time To Repair (MTTR) is used to analyze systems engine maintenance. and as a basis for determining the time interval maintenance and total cost of maintenance.Based on the results of the calculation known critical components such as Cylinder Head, Inlet valve, Gasket, Exhaust Valve Housing, Exhaust Valve. Component maintenance time intervals determined by the RCM method is as follows, Cylinder Head with interval 4458 hours, Inlet Valve with 1601 hour, Gasket with 4682 Hours, Exhaust Valve Housing with 1908 hours, Exhaust Valve with 2238 hour. Critical component consisting of Cylinder Head, Inlet Valve, Gasket, Exhaust Vave Housing and Exhaust Valve is usingSchedulled Restoration Task type of maintenance.Keywords: critical components, decision worksheet RCM, FMEA, PLTD X